KONSEP DIRI MAHASISWI BERJILBAB SYAR’I DI IAIN SURAKARTA - Lintang Ayu Fitriana; Novitasari Novitasari (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
Today there are many Muslim women who wear the hijab, but the existence of the hijab which was originally interpreted as the cover of genitalia turned into a fashion trend. The development of the times has led to the emergence of the creation and innovation of the veil model so that not a few women make the veil as a daily dress. Teenagers who are experiencing periods of self-discovery become one of the targets of the transformation of the hijab model. They switch from the ordinary hijab to the hijab syar’i by reason of following Islamic law or just following fashion trends. In this phase, teenagers are trying to understand what is part of